# help with this math problem about apples and bananas ?

if 2 apples and 3 bananas cost \$ 0.51 while 4 apples and 7bananas cost \$1.11, what is the cost of one apple and 5 bananas

i got a really horrable math teacher who just gives us work and dosnt teach us how to solve it :/

so plz explane how u did it (: THX

Update:

how do i find a ? (:

Relevance
• Anonymous
8 years ago

it is a simultaneous equation, make apples =a bananas=b

put into the word problem:

2a+3b = 0.51

4a+7b = 1.11 then solve

muliply the 1st equation by 2 it get the same value of a's ie

4a+6b = 1.02

4a+7b = 1.11

rearrange the equations to get 4a = to ......

4a=1.02-6b

4a=1.11-7b now you have 4a = ......... on both equations you can join the equations

ie 1.02-6b = 1.11-7b rearrange to get b's on on e side and numbers on the other

-6b +7b = 1.11-1.02

b= 0.09

now replace the b value into the first equation

2a+ (3*0.09) = 0.51 solve

2a= 0.24

a=0.12

check in the 2nd equation

if a=0.12

4a+7b =1.11

(4*0.12)+7b =1.11

0.48+7b =1.11

7b = 1.11-0.48

7b = 0.63

b= 0.09

therefore banana cost \$0.09

apples cost \$0.12

• Login to reply the answers
• I think the ans is \$0.57

2x+3y=0.51

4x+7y=1.11

x+5y=

solve the first 2 equ and substitute the ans in the second

• Login to reply the answers
• Anonymous
4 years ago

ok considering chocolate cake human beings have been a million/3 of the entire, meaning there have been 30 finished. it relatively is considering you're able to multiply the ten (of the human beings who like chocolate cake) circumstances 3. Algebraically it relatively is: x = finished human beings surveyed 10 = a million/3x multiply the two facets by potential of three 30 = x now you be attentive to there have been 30 human beings surveyed, merely subtract 6, 4, 6, and 10 from it. you have 4 leftover. So 4 is the respond.

• Login to reply the answers
• Anonymous
8 years ago

2a+3b = 0.51

4a+7b = 1.11

find a and b.

then find the value of (a+5b)

• Login to reply the answers
• 2a + 3b = 0.51 ---------- (1)

4a + 7b = 1.11

subtract

2a + 4b = 0.6 ---------- (3)

(3) – (1)

b = 0.09

from

2a + 4b = 0.6 ---------- (3)

2a + 0.36 = 0.6

2a = 0.24

a = 0.12

a + 5b = 0.12 + 0.45 = \$ 0.57

-----

• Login to reply the answers